Epistemologi Hadis Perspektif Syi’ah - Ida Rochmawati; Mukhammad Alfani (Al-Jadwa: Jurnal Studi Islam, 2023)
This study discusses the epistemology of hadith from the Shi'a perspective, which is a specific approach used by Shi'a scholars in understanding and assessing the quality of hadith. The Shi'a hadith epistemology takes into account the historical context and the groups involved in the transmission of hadith and pays special attention to the authority of the Imams of the ahl al-bayt in interpreting the hadith teachings. This study aims to conduct an in-depth exploration of the epistemology of hadith from the Shi'a perspective. This approach involves a review of relevant literature and research methodologies. It will also discuss the challenges and criticisms faced by the Shi'a perspective in hadith epistemology. The research method used is a comprehensive analysis of relevant literature and sources. The results of this study are expected to provide a better understanding of how the Shi'a view and apply hadith in the context of their lives and traditions. In addition, this research is also expected to provide new contributions and insights in the development of hadith science in general.